Trends in match injury risk in professional male rugby union: a 16-season review of 10 851 match injuries in the English Premiership (2002-2019): the Professional Rugby Injury Surveillance Project - West, S. W.; Starling, L.; Kemp, S.; Williams, S.; Cross, M.; Taylor, A.; Brooks, J. H. M.; Stokes, K. A. (British Journal of Sports Medicine, 2021)
Objectives: The Professional Rugby Injury Surveillance Project is the largest and longest running rugby union injury surveillance project globally and focuses on the highest level of rugby in England.